Urban Indians of Arizona Phoenix, Tucson, and Flagstaff - Chaudhuri, Joyotpaul (University of Arizona Press, 1974)
Originally published in 1974, this report offers a snapshot in time of the Native populations of three of Arizona's most populous cities, Phoenix, Tucson, and Flagstaff.